2020
DOI: 10.1177/1461444820931091
|View full text |Cite
|
Sign up to set email alerts
|

Is sexting bad for adolescent girls’ psychological well-being? A longitudinal assessment in middle to late adolescence

Abstract: Sexting, the digital transmission of sexual messages and images, has become a topic of increased interest and concern. Drawing largely on cross-sectional studies, the literature on associations between sexting and psychosocial outcomes remains inconsistent. The current longitudinal study investigated associations between adolescent girls’ sexting and two indicators of psychological well-being: symptoms of depression/anxiety and self-esteem. Responses were collected from a panel sample of 859 female Croatian se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 74 publications
1
26
0
Order By: Relevance
“…Communication between parents and youth who participate in sexting is disrupted. In general, poor family communication increases the likelihood that youth will engage in sexting (48,59). Burić, Garcia and Štulhofer (48) found in a sample of Croatian adolescents that a family environment characterised by intense quarrels, aggressive behaviour and ignoring family members was related to more frequent sexting among young people.…”
Section: Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Communication between parents and youth who participate in sexting is disrupted. In general, poor family communication increases the likelihood that youth will engage in sexting (48,59). Burić, Garcia and Štulhofer (48) found in a sample of Croatian adolescents that a family environment characterised by intense quarrels, aggressive behaviour and ignoring family members was related to more frequent sexting among young people.…”
Section: Familymentioning
confidence: 99%
“…In general, poor family communication increases the likelihood that youth will engage in sexting (48,59). Burić, Garcia and Štulhofer (48) found in a sample of Croatian adolescents that a family environment characterised by intense quarrels, aggressive behaviour and ignoring family members was related to more frequent sexting among young people. A study conducted among Canadian adolescents revealed that better parent-child communication predicted less sending of sexually explicit images (60).…”
Section: Familymentioning
confidence: 99%
“…Concerning gender, few studies showed that females are more willing to send sexts (e.g., Mitchell et al, 2012;Ybarra and Mitchell, 2014), few indicated higher sexing willingness among males (e.g., West et al, 2014;Festl et al, 2019), and some found no significant differences between the genders (e.g., Kim et al, 2020). In general, females are often considered to have a high risk of experiencing negative consequences of OSE (e.g., Bianchi et al, 2019;Burić et al, 2020). Against this background, we examined whether age and gender-related differences in OSV and OSE were identifiable in the current random-quotabased study: RQ2: Are there gender and age-related differences in OSV and OSE?…”
Section: The Current Studymentioning
confidence: 99%
“…The majority of the existing research has focused on depression and anxiety, with mixed findings emerging. Several studies identified positive associations between sexting and depression [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], while others found no significant relationship [ 11 , 12 , 13 ]. Similarly, for anxiety, while a number of studies identified positive associations [ 5 , 8 , 14 , 15 ], others reported no significant relationship [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies identified positive associations between sexting and depression [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], while others found no significant relationship [ 11 , 12 , 13 ]. Similarly, for anxiety, while a number of studies identified positive associations [ 5 , 8 , 14 , 15 ], others reported no significant relationship [ 11 , 12 , 13 ]. Beyond these two variables, sexting has been linked to higher impulsivity [ 13 ], greater psychological distress [ 4 , 16 ], higher levels of stress and lower self-esteem [ 8 ], conduct disorder [ 15 ], and borderline personality disorder features [ 17 ].…”
Section: Introductionmentioning
confidence: 99%